2009
DOI: 10.1002/hrm.20316
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment training: Recommendations to address gaps between the practitioner and research literatures

Abstract: Sexual harassment training is a common human resource activity, and the practitioner literature is replete with advice about how to implement it. Little research, however, has specifi cally explored what makes sexual harassment training effective. This paper uses what we know from general training research and theory and sexual harassment research to assess the extent to which the practitioner literature is making relevant and reasonable recommendations for sexual harassment training. We identify practitioner-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 58 publications
(97 reference statements)
1
46
0
Order By: Relevance
“…Building on the theoretical foundations developed in diversity research, we seek to increase our understanding of diversity training effects by considering also theory and research on training, on attitudes, and on attitude change and prior attempts to integrate this research with diversity training. Organizations rarely conduct in‐depth evaluations of their diversity training interventions (Hite & McDonald, ; Perry et al, ; Rynes & Rosen, ). Often, social and political pressures dictate the extent to which training is evaluated (Gutiérrez, Kruzich, Jones, & Coronado, ; Lynch, ).…”
Section: Integrating Training and Attitude Theory And Research With Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Building on the theoretical foundations developed in diversity research, we seek to increase our understanding of diversity training effects by considering also theory and research on training, on attitudes, and on attitude change and prior attempts to integrate this research with diversity training. Organizations rarely conduct in‐depth evaluations of their diversity training interventions (Hite & McDonald, ; Perry et al, ; Rynes & Rosen, ). Often, social and political pressures dictate the extent to which training is evaluated (Gutiérrez, Kruzich, Jones, & Coronado, ; Lynch, ).…”
Section: Integrating Training and Attitude Theory And Research With Dmentioning
confidence: 99%
“…Consistent with this multiple‐outcome approach to evaluation, researchers conducting narrative literature reviews of diversity training have reported evidence of beneficial results for attitude, knowledge, and skill‐based change although these results are not consistent (Curtis & Dreachslin, ; Engberg, ; Kulik & Roberson, ; Paluck & Green, ; Perry et al, ). The most common outcome evaluated within diversity training is affective based (Curtis & Dreachslin, ), but research results are mixed.…”
Section: Integrating Training and Attitude Theory And Research With Dmentioning
confidence: 99%
See 1 more Smart Citation
“…An organization's tolerance for sexual harassment contributes to sexual harassment and likely plays a role in the effectiveness of sexual harassment training. In particular, Perry et al (:821) argued that, “Employees' perceptions that the organization tolerates sexual harassment are likely to reduce the effectiveness of sexual harassment training and may also reduce their motivation to participate in training. Such climates may create perceived and actual obstacles that limit trainees' ability to transfer what is learned in the training (e.g., how to respond to sexual harassment) back to the job.” For the HR managers in charge of investigating and managing claims of sexual harassment, OTSH may signal that this aspect of a HR manager's job is not important or even discouraged by the organization, which should lead to a lack of motivation to learn how to complete these tasks effectively.…”
Section: Model Overviewmentioning
confidence: 99%
“…Relatively little research has explored the effectiveness of sexual harassment training in general (Perry, Kulik, & Field, ; Rawski, ). Furthermore, no research to date has investigated the effectiveness of sexual harassment investigation training for HR managers, despite the prominent role they play in managing this behavior in the workplace.…”
Section: Introductionmentioning
confidence: 99%